ASUHAN KEPERAWATAN PADA AN. S DENGAN INFEKSI SALURAN PERNAFASAN AKUT DI WILAYAH CILILITAN KECIL KOTA JAKARTA TIMUR - Mauriza Sativa (2022)
Background : Acute respiratory infections (ARI) can be treated independently at home by parents such as increasing rest and consuming water, but if this treatment is not appropriate and the symptoms experienced do not improve, it is feared that it will lead to complications. One of the most serious complications is death due to respiratory failure. The study was conducted to determine the causative factors and how to handle ARI with nursing care in order to reduce the incidence of ARI in children. Methods: This research uses a case study method in nursing care for An. S with ARI in Cililitan Kecil, East Jakarta. On January 22, 2021 to January 24, 2022. Data collection was obtained such as interviews, observations, physical examinations and documentation. Results: nursing diagnoses that emerged were ineffective airway clearance related to airway hypersecretion, hyperthermia associated with ARI infection, nutritional deficit related to reluctance to eat, ineffective health care related to a non-therapeutic environment. The implementation of nursing actions in accordance with priority problems and the outcome of each diagnosis for 3x24 hours the problem of airway clearance and hyperthermia can be resolved. Conclusion: the implementation given to the client is appropriate, based on nursing care. So that the diagnosis is resolved.